Fractal Flow Design: How to Design Bespoke Turbulence and Why - Sakai, Yasuhiko; Vassilicos, Christos (CISM International Centre for Mechanical Sciences, Courses and Lectures, 2016)
This book focuses on turbulent flows generated and/or influenced by multiscale/fractal structures. It consists of six chapters which demonstrate, each one in its own way, how such structures and objects can be used to design bespoke turbulence for particular applications and also how they can be used for fundamental studies of turbulent flows.